2023
DOI: 10.3390/ijms24054629
|View full text |Cite
|
Sign up to set email alerts
|

Isocorydine Ameliorates IL-6 Expression in Bone Marrow-Derived Macrophages and Acute Lung Injury Induced by Lipopolysaccharide

Abstract: Isocorydine (ICD) is a type of isoquinoline alkaloid originating from Corydalis edulis, which has been used to relieve spasm, dilate blood vessels, and treat malaria as well as hypoxia in clinic. However, its effect on inflammation and underlying mechanisms remains unclear. The aim of our study was to determine the potential effects and mechanisms of ICD on pro-inflammatory interleukin-6 (IL-6) expression in bone marrow-derived macrophages (BMDMs) and acute lung injury mouse model. A mouse model of acute lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A previous study has shown Duguetine N-oxide ( 15 ) have strong antitumor activity against HCT-8, SF-295 and MDA/MB-435 cell lines [ 36 ]. Administration of Isocorydine ( 16 ) may enhance IL-6 expression in bone marrow-derived macrophages while attenuating phosphorylation of p65 and JNK, and contribute to the protection of mice against acute lung injury induced by lipopolysaccharide [ 37 ]. The remaining 12 compounds are other alkaloids, which are rare among the natural products reported in the literature, and we will further investigate them during isolation and purification.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown Duguetine N-oxide ( 15 ) have strong antitumor activity against HCT-8, SF-295 and MDA/MB-435 cell lines [ 36 ]. Administration of Isocorydine ( 16 ) may enhance IL-6 expression in bone marrow-derived macrophages while attenuating phosphorylation of p65 and JNK, and contribute to the protection of mice against acute lung injury induced by lipopolysaccharide [ 37 ]. The remaining 12 compounds are other alkaloids, which are rare among the natural products reported in the literature, and we will further investigate them during isolation and purification.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, environmental stress and infections can directly trigger MAPK activation [96]. Recent studies have underscored the pivotal role of the MAPK pathway in the inflammatory processes in ARDS, primarily through the facilitation of the release of inflammatory cytokines and chemokines [97][98][99]. Besides, accumulating evidence have demonstrated that MAPK activation aggravates lung inflammation of ARDS by upregulating the activity of NLRP3 inflammasome and NF-κB in animal models [100][101][102].…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…The case of the isoquinoline alkaloid isocorydine ( 50 ) (also known as artabotrine and luteanin) is interesting because this product was recently shown to display marked anti-inflammatory properties and to protect mice from acute lung injury. Specifically, isocorydine ( 50 ) reduced the expression of pro-inflammatory IL-6 and attenuated the phosphorylation of p65 and JNK in bone-marrow-derived macrophages [ 80 ]. It represents a potent anti-inflammatory agent capable of regulating pro-inflammatory cytokine release via the inhibition of NFκB p65 translocation into the nucleus [ 81 ].…”
Section: Phytochemical Content Of Fissistigma Oldhamiimentioning
confidence: 99%